Metformin for Treating Gestational Diabetes: What Have We Learned During the Last Two Decades? A Systematic Review - Angeliki Gerede; Ekaterini Domali; Christos Chatzakis; Chrysoula Margioula-Siarkou; Stamatios Petousis; Sofoklis Stavros; Konstantinos Nikolettos; Evanthia Gouveri; Sotirios Sotiriou; Panagiotis Tsikouras; Konstantinos Dinas; Nikolaos Nikolettos; et al. (Life)
There has been accumulating evidence over the past two decades that metformin can be an effective treatment for gestational diabetes mellitus (GDM) in women whose diet and exercise fail to attain optimal glycemic control. The objective of this review was to comprehensively analyze all studies investigating the effectiveness of metformin compared to insulin and other drugs utilized for the treatment of GDM. After a comprehensive literature review based on PRISMA 2020, 35 studies were included after a selection process utilizing predetermined inclusion and exclusion criteria. A variety of short-term maternal and neonatal outcomes were assessed. Metformin is a highly efficient medication for attaining optimal control of blood sugar levels in women with GDM, resulting in a significant reduction in the amount of weight gained during pregnancy. Regarding additional maternal outcomes, such as pregnancy-induced hypertension and cesarean deliveries, some studies demonstrate a link between metformin and a reduced occurrence of both conditions. In contrast, others do not find an association. Regarding short-term neonatal outcomes, metformin does not exhibit any changes in gestational age at delivery. In contrast, metformin demonstrated substantial decreases in the likelihood of greater gestational birth weight and neonatal hospitalization when compared to other drugs. When compared primarily to insulin, metformin decreases the probability of several short-term outcomes related to pregnancy and newborns. Additional data are necessary for extended follow-up studies, including patients with GDM treated with metformin.